Architectural pattern of different cells lining the olfactory epithelium of long-whiskered catfish, Sperata aor (Hamilton) - Ghosh , S.K.; Chakrabarti, P. (Mesopotamian Journal of Marine Sciences, 2022)
The structural organization of the olfactory epithelium in Sperata aor was studied by light as well as scanning electron microscopy. The elongated olfactory organ comprised of 52-54 primary lamellae assorted on both sides of narrow median raphe. The middle dorsal part of the olfactory lamellae was characterised with linguiform processes. Sensory and non-sensory areas were distributed separately on each olfactory lamella. The sensory epithelium occupied in the middle linguiform process, whereas the basal part of lamellae was covered with non-sensory epithelium. The sensory epithelium was composed of morphologically distinct two types of receptor neurons either ciliated or microvillous. The non-sensory epithelium contained mucous cells and supporting cells with inconspicuous microridges. The orientation of different cells lining the olfactory epithelium was discussed in light of their functional significance.